György Ligeti - Toop, Richard (London Phaidon Press, 1999)
The Hungarian Gyorgy Ligeti (b. 1923) is one of the most highly regarded and influential of living composers. Having survived persecution as a Jew during World War II, he fled to West Germany during the Hungarian Revolution, where his early musical development was shaped by his work in the Cologne electronic studios and by the influence of Stockhausen. Rather than becoming too closely identified with any single school or movement, Ligeti's music has drawn on a divers range of sources, from the folk music of his native Hungary to African and South American World music. In works such as his Requiem, used in the film 2001: A Space Odyssey, he has proved that contemporary classical music can be accessible to a wide audience. This stimulating biography discusses Ligeti within the context of the political and cultural history of postwar Europe, and places him firmly at the forefront of musical change and innovation over the past four decades.